FORMATION AND DEVELOPMENT OF THE CREATIVE PERSONALITY OF THE FUTURE SPECIALIST (Pedagogy of Higher and Secondary Education, 2010)
The article reveals conditions of a student's creative personality development in a high school; and also qualities, peculiar to a creative personality of a future specialist are considered in the article.
Keywords: creativity; creative activity; creative personality; future specialist; cognitive activity; creative abilities